Exposure to Transit Migration, Public Attitudes and Entrepreneurship - Nicolas Ajzenman; Cevat Giray Aksoy; Sergei Guriev (Institute of Labor Economics (IZA), 2020)
Does exposure to mass migration affect economic behavior, attitudes and beliefs of natives in transit countries? In order to answer this question, we use a unique locality-level panel from the 2010 and 2016 rounds of the Life in Transition Survey and data on the main land routes taken by migrants in 18 European countries during the refugee crisis in 2015. To capture the exogenous variation in natives' exposure to transit migration, we construct an instrument that is based on the distance of each locality to the optimal routes that minimize travelling time between the main origin and destination cities. We first show that the entrepreneurial activity of natives falls considerably in localities that are more exposed to mass transit migration, compared to those located further away. We then explore the mechanisms and find that our results are likely to be explained by a decrease in the willingness to take risks as well as in the confidence in institutions. We also document an increase in the anti-migrant sentiment while attitudes towards other minorities remained unchanged. We rule out the possibility of out-migration of natives or of trade-related shocks (potentially confounded with the mass-transit migration) affecting our results. Using locality-level luminosity data, we also rule out any effect driven by changes in economic activity. Finally, we find no statistically significant effects on other labor market outcomes, such as unemployment or labor force participation.
Keywords: F22; L26; D91; O15; O10; 330; migrant routes; entrepreneurship; public attitudes; political instability